New virulent pathotypes of Sclerospora graminicola and resistance sources in pearl millet for A1 zone in India - RAJAN SHARMA; S K GUPTA; D L KADVANI; ASHA SHIVPURI; K N RAI (The Indian Journal of Agricultural Sciences, 2014)
Sixteen isolates of downy mildew (DM) pathogen (Sclerospora graminicola) collected during 2009 and 2010 from the A1 zone in India that comprises parts of Rajasthan, Gujarat and Haryana were characterized for virulence diversity along with five isolates collected during 1997 to 2005 from this region that are currently being used in the greenhouse screening. Based on DM incidence, three new pathotypes Sg 445, Sg 526 and Sg 519 identified as most virulent were selected for the greenhouse screening of 158 breeding lines under high disease pressure (>90% disease incidence in the susceptible checks). Twenty nine lines were resistant (=10% disease incidence) to at least one of the three pathotypes. Three lines were free from DM and five lines were resistant (=10% disease incidence) to all the three pathotypes, and seven lines were resistant to two of the three pathotypes. The multiple pathotype resistance identified in these breeding lines provides valuable genetic resources for breeding disease resistant pearl millet parental lines and hybrids for A1 zone in India.